2018
DOI: 10.1111/liv.13982
|View full text |Cite
|
Sign up to set email alerts
|

Intention‐to‐treat analysis of liver transplantation for hepatocellular carcinoma: The impact of pre‐existing diabetes mellitus

Abstract: Background & Aims Diabetes mellitus is known to negatively impact the outcome of liver transplant; however, data are scarce regarding risk of waitlist dropout and tumour recurrence in patients with hepatocellular carcinoma. We examined the impact of diabetes mellitus on the outcomes of candidates with hepatocellular carcinoma on an intention‐to‐treat basis. Methods Our study included 15 776 candidates with hepatocellular carcinoma diagnosis on the Scientific Registry of Transplant Recipients database from 2008… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…The cause of dialysis related to DM is another predictor of poor outcome compared with those with non-diabetes related dialysis. The exact mechanism remains unclear; however, in accordance with previous studies, DM was regarded as a predictor of poor survival in dialysis HCC patients (26)(27)(28).…”
Section: Discussionsupporting
confidence: 63%
“…The cause of dialysis related to DM is another predictor of poor outcome compared with those with non-diabetes related dialysis. The exact mechanism remains unclear; however, in accordance with previous studies, DM was regarded as a predictor of poor survival in dialysis HCC patients (26)(27)(28).…”
Section: Discussionsupporting
confidence: 63%
“…The corresponding life expectancies would be several years higher than these medians, and thus keeping with the results shown in Table 2, for example, though neither of the aforementioned studies is specific to HCC patients. Other studies such as Li et al 28 and Malik et al 29 do not report separately by age, so it is less feasible to compare with the age-specific figures given here.…”
Section: Discussionmentioning
confidence: 72%
“…A total of 23 (85.2%) studies investigated the risk of death after any HCC treatment ( Table 1 ) ( 18 - 27 , 29 - 37 , 40 - 42 , 44 ). Tumor recurrence was investigated in 14 (51.9%) studies ( Table 2 ) ( 19 , 21 , 22 , 24 , 27 , 28 , 30 , 31 , 35 , 37 , 39 - 41 , 43 ), while the risk of progressive disease was reported in 7 (25.9%) studies ( Table 3 ) ( 18 , 26 , 37 , 38 , 41 , 42 , 44 ). Overall, 5 (18.5%) studies had sample sizes of more than 1000 patients ( 25 , 34 , 37 , 41 , 44 ).…”
Section: Resultsmentioning
confidence: 99%
“…Only a study by Di Costanzo et al ( 38 ) showed longer time-to-progression (10 months vs 9 months) in 80 diabetic HCC patients treated with sorafenib compared with 233 non-diabetic HCC patients ( 38 ). Other six studies reporting data on HCC progression ( 17 , 25 , 36 , 40 , 41 , 43 ) showed an increased diabetes-associated risk (26 358 patients with vs 82 893 without diabetes) on HCC progression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation